2017
DOI: 10.1109/tuffc.2017.2683562
|View full text |Cite
|
Sign up to set email alerts
|

Blocked Elements in 1-D and 2-D Arrays—Part II: Compensation Methods as Applied to Large Coherent Apertures

Abstract: In Part I of this paper, we detected elements blocked by ribs during simulated and in vivo transcostal liver scans, and we turned those elements OFF to compensate for the loss in visibility of liver vasculature. Here, we apply blocked-element detection and adaptive compensation to large synthetic-aperture (SA) data collected through rib samples ex vivo, in order to reduce near-field clutter and to recover lateral resolution. To construct large synthetic transmit and receive apertures, we collected the individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Furthermore adding blocked elements to the beamformer reduced vessel contrast by 19% and vessel contrast to noise ratio by 10%. Subsequently a blocked element compensation method was proposed and shown to reduce reverberation clutter by 5 dB [13]. Using the two dimensional Fullwave simulation tool in the human abdomen we have previously shown that reverberation clutter is a principal source of image degradation at the fundamental frequency [2].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore adding blocked elements to the beamformer reduced vessel contrast by 19% and vessel contrast to noise ratio by 10%. Subsequently a blocked element compensation method was proposed and shown to reduce reverberation clutter by 5 dB [13]. Using the two dimensional Fullwave simulation tool in the human abdomen we have previously shown that reverberation clutter is a principal source of image degradation at the fundamental frequency [2].…”
Section: Introductionmentioning
confidence: 99%